Cutaneous phaeohyphomycosis of foot web by Curvularia lunata - Rasheeduddin, Mohammed; P, Visalakshi (Global Journal of Medical and Clinical Case Reports, 2017)
A case of cutaneous phaeohyphomycosis of the foot affecting interdigital spaces between toes in a 31 year old immunocompetent male with no history of diabetes is illustrated. Fugal elements were found in direct microscopic examination of skin scrapping. The etiologic agent was identified as Curvularia lunata based on macromophology and microscopic examination of pure culture growth. The patient was prescribed with a topical cream containing sertaconazole nitrate and oral itraconazole by the treating dermatologist. Nondermatophyte infections clinically mimic dermatophytosis, and microscopically resemble dermatophytes. Therefore, a correct identification of etiologic agent is important for appropriate treatment.